Human lung cancer neutrophils generate NETs with preserved anti-tumor cytotoxicity but impaired anti-migratory activity - Nuha Alsharif; Nuha Alsharif; Mohamad Qaisi; Merav Shaul; Naomi Kaisar-Iluz; Naomi Kaisar-Iluz; Dan Padawer; Dan Padawer; Osnath Bouhanna; Osnath Bouhanna; Yael Volman; Yael Volman; et al. (Frontiers in Immunology)
Neutrophil extracellular traps (NETs) are DNA-protein structures released during a form of programmed neutrophil death known as NETosis. While NETs have been implicated in both tumor inhibition and promotion, their functional role in cancer remains ambiguous. In this study, we compared the NET-forming capacity and functional effects of NETs derived from lung cancer (LC) patients and healthy donors (H). Neutrophils were isolated from peripheral blood and stimulated in vitro with phorbol 12-myristate 13-acetate (PMA) to induce NETosis. Isolated NETs were quantified and assessed for their cytotoxicity against A549 lung cancer cells and their impact on cancer cell migration. Whereas LC neutrophils (LCN) were less cytotoxic to tumor cells than H neutrophils (HN), their NETs maintained similar tumoricidal capacity – 41.6% ± 25.3% (LCN) vs. 46.4% ± 14.5% (HN), ns. Interestingly, we noted a correlation between the amount of NETs and their cytotoxicity to tumor cells. This effect could not be recapitulated with purified genomic DNA, inducing only 3.99% of cytotoxicity to tumor cells, and confirming that intact NETs are required for the anti-tumor activity. LCN displayed an increased frequency of NETosis following PMA stimulation, yet produced significantly fewer NETs per cell – 1569 ± 306 ng (LCN) vs. 2619 ± 313 ng (HN); p = 0.025. Reactive oxygen species (ROS) production was elevated in LC neutrophils, indicating that the NETosis defect was not due to impaired oxidative burst. LCN had increased expression of immunosuppression (PDL-1) as well as exhaustion and aging markers CD62L and CD11b). Only NETs from HN inhibited the migration of A549 tumor cells, whereas those from LCN failed to suppress, and in some cases appeared to enhance, cell motility. Our data suggest that NETs in lung cancer retain anti-tumor cytotoxicity capabilities but lose their anti-migratory capacity, highlighting their dual role in tumor biology and potential as therapeutic targets.